Piemonte - Cavallo, Maria Caterina; Cipriani, Filippo; Gerzeli, Simone; Demarteau, Nadia; Marocco, Alessia; Bamfi, Francesco (Farmeconomia. Health Economics and Therapeutic Pathways, 2008)
In Piedmont region 65% of women (aged 25-64) are screened regularly, meaning every 3 years. Considering regional tariffs and vaccine acquisition cost, the vaccination of 12-year-old girls with a 90% coverage could prevent 69 cases of cervicocarcinoma and 29 related deaths and thus results to be cost-effective (24.955 €/QALY). When the vaccination programme is extended to 16-year-old girls a further 66 cancer cases and 28 deaths could be prevented, with a very similar cost-effectiveness ratio. In Piedmont region, the net cost for woman vaccinated is 187 € for the single cohort and 190 € for the multiple cohort.